Potential Energy Curves and Dissociation Energies for Some Diatomic Molecules by Using Two Different Functions - Ayaash, Adil N.; Araak, Mais A.; Ismaeel, Fatima R. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
This study has been carried out of calculating potential energy curves (Deng-Fan potential and Morse potential) of ground state and dissociation energies of diatomic molecule (AlBr, AlI). Potential energy curves and dissociation energies depended on spectroscopic Parameters (?e, ?exe, re, ?, µ, ?,).